On following pages: 18. Sowery's Beaked Whale (Mesoplodon bidens); 19. Blainville's Beaked Whale (Mesoplodon densirostris); 20. Andrews's Beaked Whale (Mesoplodon bowdoini); 21. Spade-toothed Whale (Mesoplodon traversil); 22. Gervais's Beaked Whale (Mesoplodon europaeus). in Ziphiidae - Russell A. Mittermeier; Don E. Wilson (Deep Sea Research Part I: Oceanographic Research Papers, 2014)
On following pages: 18. Sowery's Beaked Whale (Mesoplodon bidens); 19. Blainville's Beaked Whale (Mesoplodon densirostris); 20. Andrews's Beaked Whale (Mesoplodon bowdoini); 21. Spade-toothed Whale (Mesoplodon traversil); 22. Gervais's Beaked Whale (Mesoplodon europaeus). Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Ziphiidae, pp. 326-357 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 355, DOI: 10.5281/zenodo.6608481